2020
DOI: 10.1080/15538362.2020.1828222
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and toxicity activity of aqueous extracts from various parts of breadfruit and breadnut

Abstract: Two related underutilized plants from breadfruit (Artocarpus altilis) and breadnut (Artocarpus camansi) were explored for their antioxidant and toxicity potential. Maceration with water was employed for the sake of safety and easiness. Various parts of both plants, namely leaves, fruit peel, anthocarp, and breadnut achene, were investigated. The antioxidant assays employed in this study were total phenolic and flavonoid content, total antioxidant capacity, DPPH scavenging activity, power-reducing assay, and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…They found that IC50 results of sukun leaves was 100.00 mcg/ml. The results was not accordance because the material used in their research was young and fresh Sukun leaves [21]. The results however, in accordance with the finding of Soifoini et al They found that antioxidant activity of Sukun leaves was strong.…”
Section: Resultsmentioning
confidence: 60%
“…They found that IC50 results of sukun leaves was 100.00 mcg/ml. The results was not accordance because the material used in their research was young and fresh Sukun leaves [21]. The results however, in accordance with the finding of Soifoini et al They found that antioxidant activity of Sukun leaves was strong.…”
Section: Resultsmentioning
confidence: 60%
“…Most of the studies focus on the acute toxicity of breadfruit bark and leaves which revealed no toxic reaction or mortality ( 71 , 72 ). However, Vianney et al ( 73 ) reported that the half maximal effective concentration (EC 50 ) toxicity value of breadfruit pulp extract was greater than the effective concentration for the antioxidant activity from the various assays, which confers the food safety of breadfruit pulp. Kumaraswamy and Senthamarai ( 74 ) reported that minerals, trace and heavy metal composition of breadfruit pulp using ethanol extraction was within the recommended dietary allowances (RDA) for adults established by USA National Institute of Health (NIH).…”
Section: Nutritional Composition Of Breadfruit Flour and Starchmentioning
confidence: 99%
“…Ekstrak air dari daun dan beberapa bagian buah (kulit, daging dan biji) kluwih mempunyai aktivitas antioksidan terhadap radikal DPPH dengan nilai IC50 berkisar antara 80 sampai 250 µg/mL. Ekstrak air dari biji dan daun kluwih menunjukkan aktivitas yang kuat (50-100 µg/mL), kulit buah kluwih memiliki aktivitas yang sedang (101-150 µg/mL), dan daging buah kluwih memiliki aktivitas yang rendah (>150 µg/mL) [63]. Senyawa yang berperan sebagai antioksidan antara lain β-sitosterol pada daun, sikloartenol asetat pada batang, β-amyrin asetat dan sikloeugenol pada kulit [29,30].…”
Section: Aktivitas Antioksidanunclassified